Engineering of artificial metalloenzymes based on alcohol dehydrogenase scaffold - Martins, Floriane (2021)
An ongoing objective of the chemical industry is to reduce the use of eco-destructive chemicals in cost effective and sustainable synthesis routes for high value chemicals. Biocatalysis is an established strategy for green chemistry. In this approach, artificial metalloenzymes have emerged as advanced biocatalysts, able to support a wide range of non-naturally occurring reactions in a biological environment. They are built by combining the selectivity of enzymes with the appropriate non-natural reactivity of transition metal catalysts. Current examples of these hybrids often lack control over the structure and function. They are also based on proteins with no naturally evolved binding pockets, thus lacking the advantage of proximity between a wide range of substrates and the metal catalysts. The research presented here investigates the design and development of artificial metalloenzymes for the transfer hydrogenation of imines, using the cofactor binding pocket of alcohol dehydrogenases to supramolecularly bind catalytic complexes. A computational methodology was first created to conceptualise artificial metalloenzymes, starting with two NAD(P)H-dependent enzymes: the horse liver alcohol dehydrogenase (HLADH) and the Thermoanaerobacter brockii alcohol dehydrogenase (TbADH). The in silico study was used to understand the cofactor binding site and to identify the strongest non-covalent interactions. Computationally designed library of NADH analogues were then screened as anchors for the metal catalyst, resulting in the selection of a set of lead structures. In the next step, a divergent total synthesis was proposed to create a small library of catalysts complexes via one key intermediate compound. Three iridium(III) catalysts were synthesised, based on the lead structures selected for their predicted high affinity in alcohol dehydrogenases. The complexes were then tested for their capacity to form artificial metalloenzymes. The binding affinity was investigated via competition and ITC experiments, while the catalytic activity was assessed for the transfer hydrogenation of aromatic imines. This resulted in mutual inhibition of the metal complexes and the two wild type alcohol dehydrogenases, while the TbADH mutant without catalytic zinc ion formed a working artificial metalloenzyme.